Comparison of the Clinical Outcomes between Echelette Extended Range of Vision and Diffractive Bifocal Intraocular Lenses - Xin Liu; Xiaohui Song; Wei Wang; Yanan Zhu; Danni Lyu; Xingchao Shentu; Peiqing Chen; Yibo Yu; Ke Yao (Journal of Ophthalmology)
Purpose. To compare the clinical outcomes of echelette extended range of vision (ERV) and diffractive bifocal intraocular lenses (IOLs). Methods. This is a prospective, consecutive, nonrandomized clinical trial. Seventy-three eligible patients (109 eyes) received the implantation of echelette ERV IOL (Tecnis Symfony ZXR00) or diffractive bifocal IOL (Tecnis ZMB00). 1 week, 1 month, and 3 months after surgery, visual acuities at different distances were examined. At 3 months, defocus curves, contrast sensitivities (CSs) with and without glare, optic path difference (OPD) scans, and questionnaires were evaluated. Regression analyses were applied to discover influence factors on postoperative vision. Results. ZXR00 showed better distance (P<0.05) and intermediate (P<0.001) visual acuities, while ZMB00 was better at distance-corrected near visual acuity (P<0.001). Multivariate analyses indicated that worse intermediate (P<0.001) and near vision (P=0.013) of ZMB00 might occur in patients with longer axial length. ZXR00 demonstrated smoother defocus curve and higher CSs. Superior modulation transfer function (MTF) and higher Strehl ratio (P<0.05) were shown in ZXR00. In questionnaire evaluation, ZXR00 received better outcomes in self-reported vision, Visual Function-14 (VF-14) questionnaire, Quality of Vision (QoV) questionnaire, satisfaction, and recommendation grades. Spectacle dependence did not differ between ZXR00 and ZMB00 statistically. Conclusion. ZXR00 proved to be remarkable in distance and intermediate vision, defocus curve smoothness, CSs, and visual comfort, while ZMB00 achieved better near vision. ZXR00 may attain better near vision if postoperative SE remains slightly negative. Patients with relatively longer axial length might receive less favorable intermediate and near vision after ZMB00 implantation. This trial is registered with ChiCTR-ONC-17011119.